Portable system for monitoring of regional cerebral oxygen saturation during prehospital cardiopulmonary resuscitation: a pilot study. Issue 1 (1st October 2014) - Tajima, Goro; Shiozaki, Tadahiko; Izumino, Hiroo; Yamano, Shuhei; Hirao, Tomohito; Inokuma, Takamitsu; Yamashita, Kazunori; Nagatani, Atsuko; Onishi, Mitsuo; Hirose, Tomoya; Shimazu, Takeshi; Hamasaki, Toshimitsu; et al.
Abstract : Aim: We aimed to create a system for monitoring of regional cerebral oxygen saturation (rSO2 ) in patients with prehospital cardiopulmonary arrest and clarify the changes in rSO2 during cardiopulmonary resuscitation. Methods: We measured rSO2 in cardiopulmonary arrest patients who were transferred by the emergency response vehicle of Nagasaki University Hospital. We developed a portable rSO2 monitor (HAND ai TOS), which is small enough to carry during prehospital treatment. The sensor is attached to the forehead of the patient and monitors rSO2 continuously during treatment and transfer. Results: No difficulties were experienced in monitoring rSO2 during patient treatment and transfer. Median time (interquartile range) from the emergency medical service call to emergency response vehicle arrival was 15.0 min (11.0–19.5 min). Median rSO2 on emergency response vehicle arrival at the scene was 46.3% (44.0–48.2%) ( n  = 9; median age, 74.0 years; four men, five women). Median rSO2 showed significant increase within 5 min after return of spontaneous circulation ( n  = 6, 46.6% versus 58.7%, P  < 0.05). There was no significant increase in rSO2 during prehospital cardiopulmonary resuscitation until return of spontaneous circulation was established. Conclusions: We developed an rSO2 monitoring system for use during prehospital cardiopulmonary resuscitation. The monitoring system showed a significant increase in rSO2 after return of spontaneous circulation, whereas there was no significant increase in rSO2 during cardiopulmonary resuscitation after intubation but before return of spontaneous circulation.